2020
DOI: 10.1101/2020.07.20.20158329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 antibody prevalence in health care workers: Preliminary report of a single center study

Abstract: SARS-CoV-2 has driven a pandemic crisis. Serological surveys have been conducted to establish prevalence for covid-19 antibody in various cohorts and communities. However, the prevalence among healthcare workers is still being analyzed. The present study reports on initial sero-surveillance conducted on healthcare workers at a regional hospital system in Orange County, California, during May and June, 2020. Study participants were recruited from the entire hospital employee workforce and the independent med… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 4 publications
0
20
2
Order By: Relevance
“… [37] Belgium May-June Cross Sectional Chemiluminescent Microparticle Immunoassay 1485 NA 73.1 37.03 Moderate Brant-Zawadski et al. [38] USA May-June Cross-Sectional NA 2924 42.6 72.7 54.3 High Brunner et al. [39] USA May Cross Sectional Lateral Flow Immunoassay 601 NA 72.4 NA High Chen et al.…”
Section: Resultsmentioning
confidence: 99%
“… [37] Belgium May-June Cross Sectional Chemiluminescent Microparticle Immunoassay 1485 NA 73.1 37.03 Moderate Brant-Zawadski et al. [38] USA May-June Cross-Sectional NA 2924 42.6 72.7 54.3 High Brunner et al. [39] USA May Cross Sectional Lateral Flow Immunoassay 601 NA 72.4 NA High Chen et al.…”
Section: Resultsmentioning
confidence: 99%
“…This adds on to the measures which were taken in our hospitals to provide cancer care as safe as possible [6,10-12]. The prevalence of SARS-CoV-2 antibodies among HCWs which are presumed at higher risk for infection, has been increasingly investigated [ 40 ]. In a meta-analysis of 49 studies including 127,480 health care workers overall seroprevalence of SARS-CoV-2 antibodies was 8.7% (95% CI: 6.7-10.9%) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported 0–17.4% COVID‐19 prevalence among HCWs 2–14 . However, very few have evaluated the impact of COVID‐19 on specific medical departments 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Health‐care workers (HCWs) constitute a special subgroup of the population, which is at a substantial risk of infection and is an important disease transmission source. Previous studies have reported COVID‐19 seroprevalence rates of up to 17.4% among the HCWs 2–14 . Moreover, an increasing number of reports have demonstrated that HCWs are affected by COVID‐19 with significant morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%